“Head of the Class”: equity discourses related to department head appointments at one Canadian medical school - Paula Cameron; Constance LeBlanc; Anne Mahalik; Shawna O'Hearn; Christy Simpson (Canadian Medical Education Journal, 2023)
Purpose: Equitable appointments of departmental leaders in medical schools have lagged behind other Equity, Diversity, and Inclusion (EDI) advancements. The purpose of this research was to 1) analyze how policy documents communicate changing ideas of EDI, employment equity, and departmental leadership; and 2) investigate department heads’ perspectives on EDI policies and practices.